Wildlife Trade in East Nusa Tenggara Province Based on Facebook Social Media Groups - Pramatana, Fadlan; Nainupu, Stefani Angela; Purnama, Maria M. E.; Soimin, Muhamad; Hidayat, Oki (Jurnal Manajemen Hutan Tropika, 2025)
Wildlife conservation is fundamental to mitigating the extinction due to wildlife trade. Thus, various conservation policies have been used as a reference: IUCN, CITES, and Government Policy P.106 of 2018. This research aims to record Facebook-based wildlife trade, identify the traded wildlife conservation status, and estimate the selling price. Data was taken since the group was formed until 1 July 2023. The results reveal that 107 species belonging to 53 families were recorded in 31 trading groups, comprising 82 species of aves, 17 species of herpetofauna, and eight species of mammals. Among those traded wildlife, based on P.106, 80 species are unprotected, while 27 are protected. Based on the IUCN, most traded wildlife is categorized as LC with 77 species. Some species are categorized as CR with four species, EN with 9, VU with 8, NT with 8, and NE with one species. Referring to CITES, 73 species classified as non-appendices dominate the trading groups, followed by 24 species of Appendix II, 9 of Appendix I, and 1 of Appendix III. The estimated selling price of all traded wildlife is approximately IDR 317,125,000. Governments and other conservation bodies must pay more attention to the growing Facebook-based wildlife trade, especially for protected and endangered species.